ESD goals and soft skills competencies through constructivist approaches to teaching: an integrative review - AlAfnan, Mohammad Awad; Dishari, Samira (Intelektual Pustaka Media Utama, 2024)
Recent studies claimed that the absence of a paradigm is a challenge to developing education for sustainable development and soft skills competencies. This integrative study examines stimulating these transferable and transversal competencies through constructivist approaches to teaching from the cognitive, social, radical, and critical perspectives. The study argues that the use of constructivist approaches to teaching can contribute to the achievement of education for sustainable development and soft skills competencies through the delegation of power from teachers/lecturers to students. This, in active and interactive classrooms, empowers students and builds their confidence to develop on the personal, academic, and professional levels. The use of the cognitive constructivist approach assists in developing competencies based on a clear understanding of the cognitive structures of students in a vibrant classroom environment. The use of the social constructivist approach assists in constructing individualized learning environment based on predetermined zones of proximal development in sociocultural contexts. The radical and critical constructivist approaches to teaching, through the rejection of conventional epistemologies, allow students the freedom to creatively address issues related to environmental, economic, and social sustainability. This becomes effective through the fostering of self and social awareness, challenging existing ideas, and provoking innovative thoughts that are necessary to shape a sustainable future.